2018
DOI: 10.1016/j.hpb.2018.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical hepatic resection versus wedge resection for gallbladder cancer: analysis of multi-center database

Abstract: Background: To compare anatomical hepatic resection (AHR) to wedge resection (WR) for gallbladder cancer. Methods: Hepatic resections for GBCA at 13 medical centers (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) were included. WR was defined as non-anatomical resection of 2-3 cm of the gallbladder fossa. AHR was defined as identifying and dividing the vasculobiliary pedicle for hepatic segments 4b and 5. Overall postoperative morbidity (OM), 90-day major (Clavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In another study by Pawlik et al (8) there was similar risk of disease-specific death among patients who underwent a major hepatic resection (e.g., formal segmentectomy of 4b and 5 or hemihepatectomy) and patients who underwent a hepatic wedge resection. Similar results were reported by other authors (9). It was shown that surgical margin status was the key determinant of overall outcome, and not the type of liver resection (10).…”
Section: Extent Of Liver Resectionsupporting
confidence: 87%
“…In another study by Pawlik et al (8) there was similar risk of disease-specific death among patients who underwent a major hepatic resection (e.g., formal segmentectomy of 4b and 5 or hemihepatectomy) and patients who underwent a hepatic wedge resection. Similar results were reported by other authors (9). It was shown that surgical margin status was the key determinant of overall outcome, and not the type of liver resection (10).…”
Section: Extent Of Liver Resectionsupporting
confidence: 87%